A self-confinement synthesis of a POM-decorated MOF thin film for actively hydrolyzing ethyl acetate. Issue 89 (21st October 2020) - Fang, Zhou; Chen, Danke; Li, Zhuoyi; Ma, Xu; Wan, Xinyi; Deng, Zheng; Peng, Xinsheng
Abstract : A solid acid catalyst POM@MOF thin film was prepared and utilized for the efficient hydrolysis of esters with a long durability. Abstract : Hybrid heterogeneous solid acid catalysts polyoxometalate-decorated metal organic framework (POM@MOFs) thin films were synthesized from POMs and metal hydroxide nanostrands via a self-confinement method at room temperature, which show high hydrolyzing activity (1027.5 μmol g −1 min −1 ) for ethyl acetate with durable stability and an easy recovery. This provides a general way to easily prepare nano POM@MOF thin film catalysts.